Renegotiation of Concession Contracts in Latin America - Guasch, J. Luis (World Bank, Washington, DC, 2014)
The authors construct a regulation model in which renegotiation occurs due to the imperfect enforcement of concession contracts. This enables the authors to provide theoretical predictions for the impact on the probability of renegotiation of a concession, regulatory institutions, institutional features, economic shocks, and the characteristics of the concession contracts. Then they use a data set of nearly 1,000 concessions awarded in Latin America and the Caribbean countries from 1989 to 2000 covering the sectors of telecommunications, energy, transport, and water to test these predictions. Finally, the authors derive some policy implications of their theoretical and empirical work.